2023
DOI: 10.1038/s41598-023-31852-w
|View full text |Cite
|
Sign up to set email alerts
|

Academic burnout among master and doctoral students during the COVID-19 pandemic

Abstract: The COVID-19 outbreak has had an immense impact on academic life and public health. Graduate students had experienced obligatory curfews and quarantines due to the COVID-19 outbreak directly impacting their mental health and triggering academic burnout. In this cross-sectional study, we address the issue of mental health in graduate students by relating it to the factors associated with burnout syndrome during the COVID-19 pandemic. A total of 519 graduate students from master's and Ph.D./DLA degrees across un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Despite their awareness of the spread of COVID-19, public health students were willing to take on a relatively high risk of infection to receive face-to-face instructions [6]. Postgraduates experience greater psychological burdens and employment pressures during the COVID-19 pandemic [7].…”
Section: Discussionmentioning
confidence: 99%
“…Despite their awareness of the spread of COVID-19, public health students were willing to take on a relatively high risk of infection to receive face-to-face instructions [6]. Postgraduates experience greater psychological burdens and employment pressures during the COVID-19 pandemic [7].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 90 percent of students claimed that they do not feel they receive enough emotional support from the faculty at their universities. Meanwhile, a study by Andrade et al (2023) shows that being single affected all burnout domains among graduate students across universities in Hungary and other European countries who participated in the survey. They also found high academic burnout levels among those with university dropout intentions, who were dissatisfied with the university dealing with the pandemic and did not feel supported by the university.…”
Section: Past Studies On Burnout Among Learnersmentioning
confidence: 99%
“…Ryan et al ( 2023 ) showed that burnout in medical professionals was associated with depression, anxiety, suicidality, and substance abuse. The pandemic times brought changes to academia, such as the increase in burnout (Andrade et al, 2023 ), which were explored in mental health research. A wider acceptance of internet-based therapy was discussed in literature: Svärdman et al ( 2022 ) conducted a meta-analysis showing effectiveness of internet-delivered cognitive behavioral interventions.…”
Section: Introductionmentioning
confidence: 99%